Increasing the activities of protective enzymes is an important strategy to improve resistance in cucumber to powdery mildew disease and melon aphid under different infection/infestation patterns - Zhang, Quancheng; Zhou, Menghan; Wang, Jungang (Frontiers in Plant Science, 2022)
Powdery mildew, caused by Sphaerotheca fuliginea (Schlecht.) Poll., and melon aphids (Aphis gossypii Glover) are a typical disease and insect pest, respectively, that affect cucumber production. Powdery mildew and melon aphid often occur together in greenhouse production, resulting in a reduction in cucumber yield. At present there are no reports on the physiological and biochemical effects of the combined disease and pest infection/infestation on cucumber. This study explored how cucumbers can regulate photosynthesis, protective enzyme activity, and basic metabolism to resist the fungal disease and aphids. After powdery mildew infection, the chlorophyll and free proline contents in cucumber leaves decreased, while the activities of POD (peroxidase) and SOD (superoxide dismutase) and the soluble protein and MDA contents increased. Cucumber plants resist aphid attack by increasing the rates of photosynthesis and basal metabolism, and also by increasing the activities of protective enzymes. The combination of powdery mildew infection and aphid infestation reduced photosynthesis and basal metabolism in cucumber plants, although the activities of several protective enzymes increased. Aphid attack after powdery mildew infection or powdery mildew infection after aphid attack had the opposite effect on photosynthesis, protective enzyme activity, and basal metabolism regulation. Azoxystrobin and imidacloprid increased the contents of chlorophyll, free proline, and soluble protein, increased SOD activity, and decreased the MDA content in cucumber leaves. However, these compounds had the opposite effect on the soluble sugar content and POD and CAT (catalase) activities. The mixed ratio of the two single agents could improve the resistance of cucumber to the combined infection of powdery mildew and aphids. These results show that cucumber can enhance its pest/pathogen resistance by changing physiological metabolism when exposed to a complex infection system of pathogenic microorganisms and insect pests.